2008
DOI: 10.1002/chem.200800792
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Based Telomerization of 1,3‐Butadiene with Glycerol Using Methoxy‐Functionalized Triphenylphosphine Ligands

Abstract: Glycerol is considered a potential renewable building block for the synthesis of existing as well as new chemicals. A promising route is the telomerization of 1,3-butadiene with glycerol leading to C8 chain ethers of glycerol with applications in, for example, surfactant chemistry. Recently, we reported a new set of palladium-based homogeneous catalytic systems for the telomerization of 1,3-butadiene with glycerol and found that palladium complexes bearing methoxy-functionalized triphenylphosphine ligands are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Another method of crude glycerol utilization is telomerization with 1,3-butadiene to form C 8 chain ethers, which have a wide range of applications such as useful building blocks for commercially valuable products such as detergents and surfactants (Behr et al 2009). Most recently, direct telomerization of pure as well as crude glycerol with 1,3-butadiene carried out over palladium complexes as catalysts was reported (Palkovits et al, 2008a(Palkovits et al, , 2008b.…”
Section: Glycerol Ethersmentioning
confidence: 99%
“…Another method of crude glycerol utilization is telomerization with 1,3-butadiene to form C 8 chain ethers, which have a wide range of applications such as useful building blocks for commercially valuable products such as detergents and surfactants (Behr et al 2009). Most recently, direct telomerization of pure as well as crude glycerol with 1,3-butadiene carried out over palladium complexes as catalysts was reported (Palkovits et al, 2008a(Palkovits et al, , 2008b.…”
Section: Glycerol Ethersmentioning
confidence: 99%
“…Our attention was drawn by the elegant experiments of Palkovits et al, who showed that crude glycerol can be telomerised with 1,3-butadiene in a biphasic system, in the presence of Pd-phosphine complexes. [7,8] We were interested in adapting this approach to the less active but more lucrative isoprene, the telomerisation of which would yield terpene derivatives with various possible applications in the cosmetics and detergents sectors. [9] Notably, there are only a few examples of isoprene telomerisation.…”
mentioning
confidence: 99%
“…The same group later reported a more extensive study on the Pd/TOMPP system in which the effect of the metal precursor, addition of base, butadiene/glycerol ratio as well as the ligand/metal ratio were investigated [33]. Commonly used palladium sources such as Pd(acac) 2 and Pd(OAc) 2 both worked equally well; the use of the palladium(0) complex Pd(dba) 2 resulted in a higher activity, illustrating the fact that the catalytic cycle starts with a Pd(0) species and the requirement for the Pd(II) salts to be reduced before they can enter the cycle.…”
Section: Telomerization Of Glycerolmentioning
confidence: 98%
“…At very low catalyst concentrations (0.002 mol%), PPh 3 outperformed all other ligands tested with a conversion of 58% and a TON of 30,500. Palkovits et al assessed the performance of different phosphines in the transformation of bulky nucleophiles such as glycerol to find the tris(o-methoxyphenyl)phosphine (TOMPP) ligand to be very efficient [32,33]. A recent patent awarded to Dow describes a number of ligands related to TOMPP, of which bis(2-methoxyphenyl)(4-(trifluoromethyl)phenyl)phosphine (L1) was found to be the most active in the telomerization of 1,3-butadiene with methanol [34].…”
Section: Typical Catalysts and Ligands Used In Telomerization Reactionsmentioning
confidence: 99%